Factors affecting community pharmacists' knowledge, attitudes, and practices regarding spontaneous ADR reporting in Metro Manila - Briones, Claire Therese C.; Carpio Joseph Benedict L.; Vitacion, Jose Emmanuel A.; Gutierrez, Margarita M. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Background.
Spontaneous reporting of adverse drug reactions (ADRs) is an important tool that promotes medication safety at all levels of healthcare. However. data has shown gross underreporting of ADRs all over the world. Pharmacists have an important role in pharmacovigilance: community pharmacists in particular possess specific responsibilities in the outpatient setting as they are the most accessible members of the healthcare team.

Objective.
The study aims to illustrate the knowledge on and attitude towards spontaneous reporting and their contribution to the actual practice of spontaneous reporting among community pharmacists in the different cities of Metro Manila, Philippines.

Methodology.
A descriptive cross-sectional study design was employed to collect data among 275 community pharmacists from nine (9) selected cities in Metro Manila using a validated survey questionnaire. Descriptive statistics were used to summarize the knowledge, attitude, and practice scores, whereas multiple linear regression determined the factors affecting such variables. Results. 164 community pharmacists completed the survey (59.64% response rate). The average knowledge score was 5.20 (SD ‡ 1.75, range 1-10) while the average total attitude score was 51.3171 (SD + 6.7203, range 23-65) out of 65. Almost all respondents agreed that reporting ADRs is important for patient care (98.78%, n = 162) and should be mandatory for community pharmacists (87.20%, n = 143). Reporting percentage was found to be only 43.32% (SD = 47.21), where observed ADRs were commonly mild ADRs (55.25%, n = 100) and reported via email (50.58%, n = 87). Membership to professional organizations (p-value = 0.003) and lack of awareness on ADR severity (p-value = 0.001) proportionately and inverse proportionately affected attitude scores, respectively. Fewer working hours per week (p-value - 0.002) and observing mild ADRs (p-value = 0.003) and moderate ADRs (p-value = 0.012) was associated with higher reporting ratios, whereas use of phone (text-based) methods (p-value - 0.023) translated to lower reporting ratios. Conclusion. Community pharmacists in Metro Manila possess neutral to positive attitudes towards spontaneous reporting but have low knowledge scores and do not frequently report observed ADRs. Fewer work hours per week and observing mild to moderate ADRs in practice significantly increase the ADR reporting ratio whereas the availability of a phone-based reporting method decreases the reporting ratio. Training on ADR reporting and knowledge on spontaneous reporting increases the reporting ratio of community pharmacists: however, further research must be conducted to produce more conclusive results. Efforts to promote facilitators to spontaneous reporting, such as training programs and technological advancements, may increase reporting ratios. Professional organizations (p-value = 0.003) and lack of awareness on ADR severity (p-value = 0.001) proportionately and inverse proportionately affected attitude scores, respectively. Fewer working hours per week (p-value - 0.002) and observing mild ADRs (p-value = 0.003) and moderate ADRs (p-value = 0.012) was associated with higher reporting ratios, whereas use of phone (text-based) methods (p-value - 0.023) translated to lower reporting ratios.

Conclusion.
professional organizations (p-value * 0.003) and lack of awareness on ADR severity (p-value - 0.001) proportionately and inverse proportionately affected attitude scores, respectively. Fewer working hours per week (p-value - 0.002) and observing mild ADRs (p-value = 0.003) and moderate ADRs (p-value - 0.012) was associated with higher reporting ratios, whereas use of phone (text-based) methods (p-value = 0.023) translated to lower reporting ratios. Conclusion. Community pharmacists in Metro Manila possess neutral to positive attitudes towards spontaneous reporting but have low knowledge scores and do not frequently report observed ADRs. Fewer work hours per week and observing mild to moderate ADRs in practice significantly increase the ADR reporting ratio whereas the availability of a phone-based reporting method decreases the reporting ratio. Training on ADR reporting and knowledge on spontaneous reporting increases the reporting ratio of community pharmacists; however, further research must be conducted to produce more conclusive results. Efforts to promote facilitators to spontaneous reporting, such as training programs and technological advancements, may increase reporting ratios.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2023
Keywords: Professional relationships; Pharmacists -- Philippines; Cross-Sectional Studies. -- Philippines; Pharmacovigilance